Does Combined Multichannel Intraluminal Impedance and pH (MII-pH) Testing Improve Clinical Outcomes in Children With Gastroesophageal Reflux Disease?. Issue 5 (November 2020) - Lee, Adrian L.H.; Varjavandi, Vincent; Lemberg, Daniel A.; Ooi, Chee Y.; Gupta, Nitin; Krishnan, Usha
ABSTRACT: Objectives: The aim of the study was to investigate the role of combined multichannel intraluminal impedance and pH (MII-pH) testing in clinical management of children with gastroesophageal reflux disease (GERD) by exploring the impact of treatment changes made based on MII-pH testing results on symptoms and quality of life outcomes. Methods: All patients (<18 years) referred to the Sydney Children's Hospital for MII-pH testing were recruited. Patients were classified by acid suppression therapy (AST) status (on AST and off AST) and changes in medical and surgical management were evaluated. Validated questionnaires (Pediatric Gastroesophageal Symptom and Quality of Life Questionnaire and Infant Gastroesophageal Reflux Questionnaire Revised) were administered at baseline at the time of MII-pH testing, and 4 weeks after treatment changes were made and questionnaire scores were compared. Results: Of the 45 patients recruited, 24 patients (53.3%) were off AST and 21 patients (46.7%) were on AST. MII-pH testing led to medication changes in 30 patients (66.7%). This included 15 of 24 (62.5%) in those off AST and 15 of 21 (71.4%) in those on AST. More than 98% of patients who had treatment changes showed a significant improvement in both symptoms and quality of life scores. Conclusions: Our study is one of the first pediatric studies to evaluate the clinical validity of MII-pH testing in the pediatric population referred for suspected GERD, and its ability in guiding clinical management. Our study has shown that treatment decisions guided by and based on results of MII-pH testing led to a significant improvement in symptoms and quality of life in infants and children with GERD. Abstract : Supplemental Digital Content is available in the text